A Note on the Lateral Strength of 5 mm Dia (6 SWG) Common Wire Nails in Diffprent Species for Design of Timber Structures - Pruthi, K. S.; Punhani Harbax Singh, R. K.; Bajaj, A. N. (Indian Forester, 1980)
The utility of nail as an effective fastener is particularly notable in modern timber engineering techniques. Nail-jointed timber construction, besides being simpler and economical has potentialities in enhancing the use of short length small dimensioned stocks of varied species consistent with the National objectives of efficient resources utilisation. As a pre-requisite to the successful design, the scientific study of the behaviour of nailed joints in timber structures has been extensively undertaken in this country. As a part of this research work the lateral nail strength properties of 5 mm dia nails in different species of timber have been determined. These values contained in this paper would enable the designers to determine exact economic sections of various structural members for roofs, beams and column supports etc. methodology followed in arriving at safe loads is also described in this paper.